KNOWLEDGE OF SIDE EFFECTS AND ITS ASSOCIATION TO COMPLIANCE IN IRON TABLETS CONSUMPTION AMONG THIRD TRIMESTER PREGNANT WOMEN - Nurhidayah Nurhidayah; Dwi Handayani; Pratiwi Puji Lestari; Fitria Yulastini (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: To improve the quality of teaching, teachers should be able to plan the preparation of teaching and at the same time also be able to do so in the form of teaching and learning interactions. The success of learning is influenced by several factors, one of them is the motivation.The motivation will affect the success of learners. A student who has a high enough intelligence can fail due to lack of motivation. Aims: The purpose of this researchis to determine the relationship of students' perception about the use of teaching method and learning motivation and achievement of midwifery D III in midwifery care in pregnancy course. Methods: Observational analytic research with cross sectional approach was conducted in the Diploma Program of Midwifery of Universitas RESPATI on May 29, 2014. The sampling technique was aproportional random sampling with a sample of 138 college students.Statistical data analysis was spearman rank test. Results: The data shows there is no relationship between students’ perception on teaching method andstudents' achievement (p value >0.05). However, a very significant relationship (p value < 0.01) was found between students’ motivation and their academic achievement. Conclusion: The findings suggest that among the midwifery students in Diploma Program of Universitas Respati, to achieve better academic performance, the students need motivation (internal or external) to easier understand the academic subject.It is expected to the teachers, especially lecturers to develop the teaching methods and materials in accordance with student motivation in learning.